Collagen-Polyvinyl Alcohol-Indomethacin Biohybrid Matrices as Wound Dressings - Ștefania Marin; Mădălina Georgiana Albu Kaya; Mihaela Violeta Ghica; Cristina Dinu-Pîrvu; Lăcrămioara Popa; Denisa Ioana Udeanu; Geanina Mihai; Marius Enachescu (Pharmaceutics, 2018)
The aim of this study is to design, develop and evaluate new biohybrid sponges based on polymers (collagen and polyvinyl alcohol) with and without indomethacin as anti-inflammatory drug model to be used for tissue regeneration in wound healing. Type I fibrillar collagen in the form of a gel and different concentrations of polyvinyl alcohol were mixed together to prepare composite gels. Both control samples, without indomethacin and with indomethacin, were obtained. All samples were crosslinked with glutaraldehyde. By freeze-drying of hydrogels, the spongious forms (matrices) were obtained. The matrices were characterized by FT-IR spectroscopy, scanning electron microscopy (SEM), water absorption, enzymatic degradation and in vitro indomethacin release. The pharmacological effect of the spongious biohybrid matrices was determined on an experimental model of burns induced to Wistar rats. The SEM images showed a porous structure with interconnected pores. Collagen sponges present a structure with pore sizes between 20 and 200 µm, which became more and more compact with polyvinyl alcohol addition. The FT-IR showed interactions between collagen and polyvinyl alcohol. The enzymatic degradation indicated that the most stable matrix is the one with the ratio 75:25 of collagen:polyvinyl alcohol (ACI75), the other ones being degradable in time. The kinetic data of indomethacin release from matrices were fitted with different kinetic models and highlighted a biphasic release of the drug. Such kinetic profiles are targeted in skin wound healing for which important aspects are impaired inflammation and local pain. The treatment with sponges associated with anti-inflammatory drug had beneficial effects on the healing process in experimentally induced burns compared to the corresponding matrices without indomethacin and the classical treated control group.